Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

(x+3)(x2 – 3x + 4)
help simplify the expression.​


Sagot :

Answer:

x³-5x+12

Step-by-step explanation:

(x+3)(x²-3x+4)

=x³-3x²+4x+3x²-9x+12

collect like terms

=x³-3x²+3x²+4x-9x+12

=x³-5x+12

Answer:

(x+3)(x2-3x+4)

x3-3x2+4x+3x2-9x+12=0

x3-3x2+3x2+4x-9x+12=0

x2-5x+12=0

x2-5x=-12

x2÷x-5x÷x=-12

1-5=-12

-4=-12

-4÷-4=-12÷-4

x=3